Awake brain MRSI reveals anesthetic sensitivity and regional aging effects on [13C]bicarbonate metabolism in mice - Ono, Maiko; Kono, Rena; Hirata, Kosei; Saito, Keita; Nakao, Motonao; Takakusagi, Yoichi; Araki, Rikita; Sumiyoshi, Akira; Takado, Yuhei (Frontiers in Neuroimaging, 2025)
Abnormalities and alterations in the glycolytic pathway in the pathology of neurodegenerative diseases and brain aging have received much attention, as clinical applications of proton-based magnetic resonance spectroscopy (MRS) have recently illuminated the elevation of lactate concentrations in the brains of patients with neurodegenerative diseases, including Alzheimer’s disease. Hyperpolarized [1-13C]pyruvate MRS has shown promise for neurological applications because it enables the real-time in vivo detection of glycolysis and oxidative phosphorylation flux. In studies of the mouse brain using hyperpolarized [1-13C]pyruvate, there are few reports that the signal of [13C]bicarbonate, a product of oxidative phosphorylation metabolized from [1-13C]pyruvate, was detected using MR spectroscopic imaging (MRSI) that allows spatial mapping of metabolism, although there have been reports of [13C]bicarbonate signals being detected by pulse-acquire sequences in the entire brain. In the present study, we compared hyperpolarized [1-13C]pyruvate metabolism between the brains of awake and isoflurane-anesthetized mice using a custom-made awake mouse restraint device with MRSI. Although the signal for [1-13C]lactate, a product of glycolysis metabolized from [1-13C]pyruvate, was detectable in multiple brain regions that include the orbitofrontal cortex and hippocampus in both awake and anesthetized mice, the signal for [13C]bicarbonate metabolized from [1-13C]pyruvate was only detectable in the brains of awake mice. Moreover, a comparison of hyperpolarized [1-13C]pyruvate metabolism in young and aged mouse brains using awake MRSI detected age-related decreases in oxidative phosphorylation flux in brain regions that include the hippocampus with variations in the extent of these changes across different brain regions. These results demonstrate that hyperpolarized [1-13C]pyruvate MRSI under awake conditions is useful for the spatial detection of abnormalities and alterations in glycolysis and oxidative phosphorylation flux in the brains of mice. Thus, the use of hyperpolarized [1-13C]pyruvate MRSI has potential in pathological and mechanistic studies of brain diseases and brain aging.